2020
DOI: 10.1088/2053-1591/ab771b
|View full text |Cite
|
Sign up to set email alerts
|

Improving durability of glass fiber reinforced polymer composites by incorporation of ZnO/OMMT nanoparticles subjected to UV radiation and hygrothermal aging

Abstract: Glass fiber reinforced polymer (GFRP) composites have high sensitivity to UV radiation, temperature, and moisture, and these factors lead to the decrease of mechanical properties. This study attempts to modify unsaturated polyester (UP) and vinylester (VE) resins with nano zinc oxide (ZnO) and organomontmorillonite (OMMT), in order to improve UV radiation resistance and hygrothermal resistance. The nano ZnO/OMMT modified UP and VE based GFRP composites were subjected to UV radiation and hygrothermal aging at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Their results indicated that the composites containing of encapsulated halloysite nanotubes were able to heal the scratches completely and recover the structural functions in the presence of sunlight. Xu et al 25 improved durability of glass fiber reinforced polymer composites by incorporation of nano ZnO and organo-montmorillonite subjected to UV radiation and hygrothermal aging. They could increase the flexural strength and interlaminar shear strength by 26.5% and 27.2%, respectively in hygrothermal condition.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the composites containing of encapsulated halloysite nanotubes were able to heal the scratches completely and recover the structural functions in the presence of sunlight. Xu et al 25 improved durability of glass fiber reinforced polymer composites by incorporation of nano ZnO and organo-montmorillonite subjected to UV radiation and hygrothermal aging. They could increase the flexural strength and interlaminar shear strength by 26.5% and 27.2%, respectively in hygrothermal condition.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating nanoclay helped in a significant drop in water uptake behavior in nanocomposites compared to neat epoxy composites. Xu et al [30] worked on the durability enhancement of polymer/glass-fiber composite with the addition of ZnO/OMMT nanofillers. The nanocomposites were subjected to hygrothermal aging (30 C, 50 C, and 60 C) and UV radiations for 90 days.…”
Section: Introductionmentioning
confidence: 99%